The relationship between sociodemographic characteristics, lifestyle, and diet quality with diabetes risk in overweight and obese Turkish adults - Rahime Evra Karakaya; Emine Elibol (BMC Public Health)
Abstract Background Obesity and certain associated environmental factors increase the risk of type 2 diabetes mellitus (T2DM). This research aims to evaluate the relationship between sociodemographic characteristics, lifestyle, and diet quality with diabetes risk in overweight and obese Turkish adults. Methods A questionnaire form including sociodemographic characteristics, lifestyle, body weight and height was applied. Finnish Diabetes Risk Score (FINDRISC) tool was used to identify the risk of T2DM. Dietary assessments were made by 24 h dietary recall and diet quality was evaluated by Healthy Eating Index-2015 (HEI-2015). Results According to FINDRISC score, 38.1% of adults were at mild risk, 21.9% were at moderate risk, and 20.9% were at high risk. In regression model, factors such as low educational level, being married, being employed, smoking, and the presence of comorbidities were found to increase the risk of developing diabetes. Each unit decline in HEI-2015, the risk of diabetes increased by a factor of 0.983. Conclusions Sociodemographic factors, lifestyle, and diet quality significantly contribute to the increased risk of diabetes in overweight and obese Turkish adults. This trial was registered at clinicaltrials.gov with number NCT06614075 and registration date of 26 September 2024, retrospectively registered.